1990
DOI: 10.1099/0022-1317-71-12-2915
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation of Japanese Encephalitis Virus in Nature

Abstract: Forty-six strains of Japanese encephalitis (JE) virus from a ovariety of geographic areas in Asia were examined by primer-extension sequencing of the RNA template. A 240 nucleotide sequence from the pre-M gene region was selected for study because it provided sufficient information for determining genetic relationships among the virus isolates. Using 12 % divergence as a cutoff point for virus relationships, the 46 isolates fell into three distinct genotypic groups. One genotypic group consisted of JE virus is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
158
2
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(167 citation statements)
references
References 17 publications
6
158
2
1
Order By: Relevance
“…The results of pair-wise comparisons of 240 nucleotides from the 67 JE virus isolates from different geographic regions indicated that the 12 Thai strains belonged to genotype 1 of Chen et al (9), which contains virus strains from northern Thailand and Cambodia (Fig. 2).…”
Section: Genotype Determination Of 12 Thai Strains From Prm Nucleotidmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of pair-wise comparisons of 240 nucleotides from the 67 JE virus isolates from different geographic regions indicated that the 12 Thai strains belonged to genotype 1 of Chen et al (9), which contains virus strains from northern Thailand and Cambodia (Fig. 2).…”
Section: Genotype Determination Of 12 Thai Strains From Prm Nucleotidmentioning
confidence: 99%
“…By pair-wise sequence comparison of 67 nucleotide sequences, a dendrogram of the virus relationship was constructed with the aid of the "Cluster Analysis" computer program (48). The prM nucleotide sequence information of 56 JE strains was obtained from previous publications (9,10). The nucleotide sequence data of the E protein genes of Nakayama, Beijing-1, Kamiyama, 691004 and Muar were obtained from Hasegawa et al (18) and ThCMAr4492 and ThCMAr6793 from our previous report (1).…”
Section: Two Primers Je317smentioning
confidence: 99%
See 1 more Smart Citation
“…Genotype I is found primarily in Laos, northern Thailand, Cambodia, and Malaysia; Genotype II consists of isolates from southern Thailand, Malaysia, and Indonesia; Genotype III appears to be the most widely distributed and includes isolates from Japan, Korea, China, Malaysia, Philippines, Indonesia, India, and Sri Lanka; and Genotype IV appears to be restricted to Indonesia. [8][9][10] Comparison of the genetic sequence of the 1995 isolates of JE virus in the prM region revealed they probably had a common source and were most closely related to a 1970 isolate from Malaysia and a 1981 isolate from Indonesia, both of which belonged to Genotype II. 5 Sequence comparison of an overlapping region of the non-structural and 3Ј untranslated region (NS5-3Ј UTR) confirmed the relationship between the Australian, Indonesian, and Malaysian isolates, and also revealed the Australian isolates had a unique eleven base deletion immediately following the stop codon in the 3Ј untranslated region.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the vast majority of work on flaviviruses, including vaccine studies and phylogenetic analyses in which genotypes were identified and sometimes correlated with disease severity (Chen et al, 1990;Leitmeyer et al, 1999;Rico-Hesse, 1990), has rested on the implicit assumption that evolution in the family Flaviviridae is clonal, with diversity generated through the accumulation of mutational changes.…”
Section: Introductionmentioning
confidence: 99%